Regeneration technique for the spent bleaching clay: oil extraction and activation - Hanipah, Abu (Penerbit UTM, 2007)
Malaysia has become the biggest palm oil producer and exporter with total cultivated land area about 4.3 million hectares. It has the capability to generate about 16.5 millions tonne of palm oil per year (MPOB, 2007). In order to process the palm oil, it has 434 palm oil mills operating throughout the Malaysia with 49 mills concentrating in processing palm kernel and 66 mills for refinery process.